Late Quaternary water temperature variations of the Northwest Pacific based on the lipid paleothermometers TEXH86, UK37 and LDI - Jonas, A.; Schwark, Lorenz; Bauersachs, T. (Pergamon, 2017)
© 2017 Elsevier Ltd The Kuroshio Current (KC) and Oyashio Current (OC) are the two major western boundary currents of the Pacific Ocean and their interplay exerts a major control on the climate evolution of the northwestern Pacific region as well as East Asia. Although millennial scale variations in the strength and flow pattern of the KC are well documented, only little is known on the long-term evolution of this ocean current and its role in affecting regional and global climate over geological time scales. Here, we present surface and thermocline temperature records covering the last two glacial-interglacial cycles of IODP (Integrated Ocean Drilling Program) Site C0011, SE of Japan, using the lipid paleothermometers TEX H 86 (tetraether index of tetraethers consisting of 86 carbon atoms), U K´ 37 (unsaturated ketone index) and LDI (long-chain diol index). Lower average water temperatures (20.1–20.7 °C in TEX H 86 , 21.6–22.0 °C in U K´ 37 , and 20.7–21.9 °C in LDI) during marine isotope stages (MIS) 2 and 6 are considered to indicate a reduction in warm water mass export from the Western Pacific Warm Pool (WPWP) to northern mid-latitudes via the KC due to decreased subtropical gyre circulation in the North Pacific. A synchronous southward displacement of the KC/OC interfrontal zone resulted in an overall stronger influence of colder and more polar waters at Site C0011. MIS 1, 3 and 5 are characterized by generally higher water temperatures (21.7–22.1 °C in TEX H 86 , 23.2–24.3 °C in U K´ 37 , and 23.1–24.3 °C in LDI), likely reflecting an increased northward transport of subtropical waters to the study site. Higher Holocene than Eemian water temperatures are attributed to a stronger KC and the formation of its short meander south of Japan, whereas a less strong KC during the Eemian likely favored the formation of the large meander path. Better correlations between the different lipid paleothermometers during cold MIS are considered to indicate more similar production seasons and habitat depths of the biological proxy sources with the latter factor likely driven by thermocline shoaling.